Anomali Kesusilaan: Tafsir Moralitas dalam Novel Pendosa yang Saleh Karya Royyan Julian - Maghfiro, Nuzula; Amita Krisnandini, Lintang (Udayana University, 2025)
This study analyzes The Righteous Sinner by Royyan Julian using Lucien Goldmann's genetic structuralism theory of literary sociology to explore the moral contradictions of its characters. Through qualitative analysis of excerpts, the research identifies contradictions in characters' actions and dialogues. The results of this study indicate an anomaly in moral and ethical values as portrayed through the characters. The moral complexity in the characters' actions, which contrasts with the societal image attached to them, indicates an attempt to explore the human dimension and previously unexplored boundaries. This research is beneficial in providing a deeper understanding of how literary works can represent social realities and the struggle of moral values within society, as well as serving as a reference for literary studies that focus on the relationship between the structure of a work and the structure of society.